1996
DOI: 10.1002/(sici)1096-9888(199605)31:5<537::aid-jms330>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Solvation Energies and Electrospray Mass Spectrometric Response Factors. Study by Electrospray Mass Spectrometry of Supramolecular Complexes in Thermodynamic Equilibrium in Solution

Abstract: Electrospray mass spectrometric (ESMS) studies of solutions of alkali metal chlorides have shown that the value of the solvation energy is a key parameter in the ion yield in ESMS. The ESMS response factor, kM, of the ion is linked to the solvation energy, EM, of the ion by a simple mathematical relationship, kM = C exp(‐0.015 EM), where C is a constant depending on the ion charge, the ion concentration and the instrument parameters. In two competition experiments, the relative affinities of Na+, K+, Rb+ and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
134
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(138 citation statements)
references
References 2 publications
4
134
0
Order By: Relevance
“…It has also been observed that proteins or peptides of comparable size and amino acid content have similar electrospray ionization response factors. [30] For compounds that bind to target molecules with similar-type binding mechanisms, it is likely that they have similar gas-phase stabilities, and consequently allow a relative assessment of the binding affinities of the antibiotics towards the bacterial cell-wall-mimicking ligands. [31] Given the aforementioned considerations, we employed mass spectrometry to investigate the noncovalent complexes formed between the glycopeptide antibiotics and LII, and compared them with those formed with the traditional KAA model peptides.…”
Section: Resultsmentioning
confidence: 99%
“…It has also been observed that proteins or peptides of comparable size and amino acid content have similar electrospray ionization response factors. [30] For compounds that bind to target molecules with similar-type binding mechanisms, it is likely that they have similar gas-phase stabilities, and consequently allow a relative assessment of the binding affinities of the antibiotics towards the bacterial cell-wall-mimicking ligands. [31] Given the aforementioned considerations, we employed mass spectrometry to investigate the noncovalent complexes formed between the glycopeptide antibiotics and LII, and compared them with those formed with the traditional KAA model peptides.…”
Section: Resultsmentioning
confidence: 99%
“….O4 ϭ 2.636(3) Å]. The slightly deformed crown conformation of the uncomplexed host [17] changes in response to the complexation of the guest. The inclusion of the cation in the cavity and the simultaneous inclusion of the anion at the lower rim induces a change from the slightly deformed crown of the free host to the nearly perfect C4 crown observed here in [N(CH 3 ) 4 1]Br.…”
Section: Complex Formationmentioning
confidence: 99%
“…According to Ralph et al [16], however, ionization efficiency and mass discrimination effects are expected to be limited for inclusion complexes of a large host with a relatively small charged guest and can be neglected. The influence of the solvation energy has been studied by Leize et al; they reported that the ESI-MS yielded a true image of the proportions of different species of alkali metal complexes present in thermodynamical equilibrium in solution [17]. In addition, mass spectrometry is a fast and accurate method of analysis and provides easily gathered but dependable stoichiometric information about cationic species.…”
mentioning
confidence: 99%
“…E xtensive solution and gas phase investigations of alkali metal ion cationization of small podands, which are linear or ring structures with repeating (-Carbon-Carbon-Heteroatom-) units, have lead to improved understandings of host-guest complexation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20]. Factors involved in the solution phase molecular recognition are solvation enthalpy and entropy for both species and the number of atoms from the ligand that are involved with the binding of the metal ion, plus any conformational change of the ligand between its unbound and bound forms [21].…”
mentioning
confidence: 99%